Beneficial outcomes and features of playgroup participation for children and adult caregivers: A systematic review of the literature. (November 2022) - McLean, Karen; Edwards, Susan; Katiba, Timothy; Bartlett, Jacinta; Herrington, Michele; Evangelou, Maria; Henderson, Michael; Nolan, Andrea; Skouteris, Helen
Abstract: Playgroups are a unique form of early childhood education and care provision involving children and their adult caregivers attending and participating in shared play. Playgroups are known to promote positive social and educational outcomes for children and adult caregivers (e.g., parents, carers, or kinship members), however, the playgroup research is not well summarised for confirming beneficial outcomes for children and their caregivers, alongside insight into the features of provision pertaining to playgroups in practice. To advance the field, this systematic literature review sought to identify the beneficial outcomes of playgroup participation for children and their adult caregivers and any indicated primary and secondary features of playgroup provision in practice. Forty studies met the inclusion criteria. Findings indicated several beneficial outcomes for children and adult caregivers, including amongst others, social and emotional beneficial outcomes for children and social connections and support for adult caregivers. Findings also suggested four primary and three secondary features of provision. Primary features were facilitator, play activities, safe welcoming space and routines and structure. Secondary features were service networks, materials and venue. Analysis of the reported measures used in the studies to establish beneficial outcomes for children and adult caregivers show a reliance on interviews and non-validated measures. Further research is needed using validated measures and to establish how beneficial outcomes of playgroup participation for children and adult caregivers are related to features of provision in practice. Highlights: The review identifies studies which found beneficial outcomes of playgroups. The features of playgroups in studies identifying beneficial outcomes are examined. Four primary and three secondary features of playgroup were identified. Primary features are facilitator, play activities, safe welcoming space, routines and structure. Secondary features are service networks, materials and venue.